The Importance of Taking a Patient-Centered, Community-Based Approach to Preventing and Managing Frailty: A Public Health Perspective - Adja, Kadjo Yves Cedric; Lenzi, Jacopo; Sezgin, Duygu; O'Caoimh, Rónán; Morini, Mara; Damiani, Gianfranco; Buja, Alessandra; Fantini, Maria Pia (Frontiers in Public Health, 2020)
Across the world, life expectancy is increasing. However, the years of life gained do not always correspond to healthy life years, potentially leading to an increase in frailty. Given the extent of population aging, the association between frailty and age and the impact of frailty on adverse outcomes for older people, frailty is increasingly being recognized to be a significant public health concern. Early identification of the condition is important to help older adults regain function and to prevent the negative outcomes associated with the syndrome. Despite the importance of diagnosing frailty, there is no definitive evidence or consensus of whether screening should be routinely implemented. A broad range of screening and assessment instruments have been developed taking a biopsychosocial approach, characterizing frailty as a dynamic state resulting from deficits in any of the physical, psychological and social domains, which contribute to health. All these aspects of frailty should be identified and addressed using an integrated and holistic approach to care. To achieve this goal, public health and primary health care (PHC) need to become the fulcrum through which care is offered, not only to older people and those that are frail, but to all individuals, favoring a life-course and patient-centered approach centered around integrated, community-based care. Public health personnel should be trained to address frailty not merely from a clinical perspective, but also in a societal context. Interventions should be delivered in the individuals' environment and within their social networks. Furthermore, public health professionals should contribute to education and training on frailty at a community level, fostering community-based interventions to support older adults and their caregivers to prevent and manage frailty. The purpose of this paper is to offer an overview of the concept of frailty for a public health audience in order to raise awareness of the multidimensional aspects of frailty and on how these should be addressed using an integrated and holistic approach to care.